Mazhab Akidah dan Sejarah Perkembangan Tasawuf Ba’lawi - Kholili Hasib (Universitas Darussalam Gontor, 2017)
The people of Ba’lawi or Bani Alawi or whose ancestors came from Hadramaut, Yemen, had a significant influence on Islamic da’wah in the archipelago of Nusantara, where the majority of the population adheres to the Islamic School of Imam Syafi’i. One of that influence can be traced in the aspect of Sufism. The peole of Ba’lawi are descendant of the Prophet Muhammad PBUH-in Indonesia called Habib-which were having quite respectable position among the followers of Imam Syafi’i. In their movement, they have an important role in the internalization of Sufism pattern. Sufism of Ba’lawi has become a ‘fence’ and an effective media of da’wah. As the ‘fence’, the Sufism they called by Tari>qah Ba> ‘lawi> contains the doctrines of aqidah and amaliyah in order to protect the aqidah of Ahlusunah wal Jama’ah (Aswaja) through a spiritual path. As’ containers’, the simple and modern Tari>qah Ba> ‘lawi> becomes the main attraction for the Muslims to follow their teaching of aqidah. The approach of morality and mysticism are very interested for residents of the archipelago. Functionally, a number of certain prayers in the tari>qah has a specific purpose to protect Ba’lawi descent and Muslims from some teaching of non-Aswaja. However, some accusation related to the relationship between Ba’lawi and Shi’a are quite interesting to discuss. Especially, when the Ba’lawi preachers began to expand their message to the expansion of the archipelago, when the kingdom of Perlak become the main destination. How far are the people of Ba’lawi accused of having relationship with Syi’a? So, how do Muslim researchers react toward this potentially fatal distortion of the facts? This will be the topic of the study written by the author of this paper.",